RESPON PERTUMBUHAN TANAMAN KANGKUNG (Ipomoea reptans Poir) TERHADAP BERBAGAI INTERVAL PENYIRAMAN DAN DOSIS PEMUPUKAN NPK PADA MEDIA TANAH + ARANG SEKAM (1+1) - Toyip Toyip (Agropet, 2013)
This experiment aims to study the response of kangkoong plants to various planting media composition. The experiment was conducted in Maret to April 2011 in the Greenhouse at University Farm, IPB.  It was arranged with two factor, the first factor is interval of irrigation and second factor is rate of NPK fertilizer and three replications. Implementation of the experiment based on Two Factors Experiments in Completely Randomized Design. Experimental results show that, the media consisting of soil and rice husk with a ratio of 1:1, with gives the best results on plant height and yield of kangkung.